2009
DOI: 10.3171/2008.4.17569
|View full text |Cite
|
Sign up to set email alerts
|

Glioma surgery using a multimodal navigation system with integrated metabolic images

Abstract: The authors' preliminary intrainstitutional comparison between the 2 navigation systems suggested the possible premise of multimodal navigation. The multimodal navigation system using MET-PET fusion imaging is an interesting technique that may prove to be valuable in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 30 publications
1
59
0
1
Order By: Relevance
“…17,19,[25][26][27][28][29][30][31] We attempted to approach this important issue in the present report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,[25][26][27][28][29][30][31] We attempted to approach this important issue in the present report.…”
Section: Discussionmentioning
confidence: 99%
“…This image-histological comparison will logically support the utility of 11 C-methionine PET image-guided surgery for cytoreduction of gliomas with the possibility of identifying the tumor/nontumor border, although clinical data for PETguided resection is limited at present. 17,30 The second aspect of the present study was to reveal the relationship between 5-ALA-induced fluorescence and histology. The results showed that cell density and Ki-67 labeling index were higher in the fluorescence-positive area than in negative area.…”
mentioning
confidence: 99%
“…For this application, amino acid and nucleoid tracers are better suited (123)(124)(125)(126)(127). Several studies suggested that outcomes are better for patients in whom 11 C-MET or 18 F-FET PET coregistered to MRI are applied for treatment planning and follow-up than for patients diagnosed by MRI alone (123)(124)(125)(126)128). In the follow-up and for the management of patients with brain tumor, the differentiation between recurrent tumor as a sign of treatment failure and necrosis as an indicator of success is essential.…”
Section: Monitoring Treatment Effects Petmentioning
confidence: 99%
“…Multi-model fusion imaging technology, as a new tool, has widely been used in neurosurgery recently (18). It can merge the computed tomography (CT) and MRI images together; build 3D framework of brain structure; combine with MRI angiography, CT angiography, DTI, magnetoencephalography, and other functional magnetic resonance imaging; integrate into the navigation system, and complete individualized preoperative plan (23). Functional magnetic resonance imaging confirms the orientation of cortical motor and language area.…”
Section: Casementioning
confidence: 99%